(In)formational Cities. (November 2015) - Leach, Neil
Abstract : Is the focus on mass customisation with its emphasis on generating architectural form misguided? Is the future of our cities instead more likely to be directed towards the capacity to accommodate informational systems and the possibilities that new technologies afford to redesign existing buildings? Architectural author, professor and guest‐editor of the Digital Cities (July/August 2009) and Space Architecture (November/December 2014) issues of AD, Neil Leach appeals to architects to turn away from their fixation with the material properties of the built environment and customise their own approaches to analysis and design to fully embrace the computational revolution that has taken place.